Integrating the Entrustable Professional Activities Framework into Undergraduate Medical Education - Saurabh RamBihariLal Shrivastava; Shubhada Gade; Sunita Vagha (Wolters Kluwer Medknow Publications, 2024)
Competency-based medical education plays a crucial role in empowering medical students to deliver quality-assured patient-centered care in their future clinical practice. The purpose of the current article is to explore the benefits of entrustable professional activities (EPAs) in medical education delivery, devise a step-wise plan to integrate EPAs in undergraduate medical education, and identify the potential challenges and the potential solutions to overcome them. The use of EPAs in medical education has been linked with merits specific to students, teachers, and the health-care delivery system. The act of implementing EPAs in undergraduate medical education essentially requires the adoption of a systematic and well-planned process to integrate them into the existing curriculum and overall educational framework. In conclusion, the integration of EPAs into undergraduate medical education can redefine the future of education and health-care delivery. However, we have to be proactive in addressing the identified challenges, and we must adopt a comprehensive and collaborative approach involving different stakeholders to empower medical students to the challenges of the health sector.